Chatbots in marketing = Chatboty w marketingu - Kaczorowska-Spychalska, Dominika (Zielona Góra: Faculty of Economics and Management Press)
The role of digital technologies, especially the Internet of Things (IoT) and Artificial Intelligence (AI), increasingly become a key element of diverse interactions between brands and consumers. Homo Cyber Oeconomicus, one of the potential stages of ongoing consumer?s evolution, lives between processes of dehumanization of the surrounding world and humanization of digital technologies. While remaining in a constant contact with smart devices, systems and algorithms, they are looking for new values and meanings, which are a metaphor of their desires, fears and behaviors.
Keywords: technologie cyfrowe; chatboty; zachowania konsumenckie; marketing; digital technologies; consumer behavior